Effect of hexanal vapour on longan fruit decay, quality and phenolic metabolism during cold storage - Porntip Thavong (2018)
The effects of postharvest treatment with hexanal vapour on longan fruit decay, quality, hexanal residue, phenolic compound content, and polyphenoloxidase (PPO) and peroxidase (POD) activities were studied during storage at 5 °C for 30 days. Hexanal exposure for 2 h at 900 μL L-1 before cold storage reduced the percentage of fruit with decay and was deemed the optimum treatment. Hexanal exposure resulted in a pericarp that was more reddish brown and less intense in colour. Hexanal residue in the pericarp and aril of fumigated fruit was several fold higher than that of nonfumigated fruit, although levels were low at the end of cold storage. Electrolyte leakage of pericarp increased during 5 °C storage and was further increased by hexanal exposure. Hexanal reduced pericarp phenolic content, and increased PPO and POD activities. Overall, use of hexanal vapour reduced postharvest disease of longan fruit but increased the likelihood of pericarp browning. © 2010 The Authors. International Journal of Food Science and Technology © 2010 Institute of Food Science and Technology.